STUDI FENOMENOLOGI: PENGALAMAN KELUARGA MERAWAT ANGGOTA KELUARGA DENGAN PENGOBATAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS DUMBAYABULAN - Yusuf, Nur Ayun R.; Dulahu, Wirda Y.; Rahim, Nirwanto K.; Mohamad, Parlan (An Idea Health Journal, 2024)
Tuberculosis is one of the top 10 infectious diseases that cause death worldwide and causes more deaths than HIV/AIDS annually. Several things support the success of treatment, considering that the duration of tuberculosis treatment is at least six months, one of which is family support. Therefore, is is necessary to determine the family’s experience treating tuberculosis patients. This research aims to determine the experience of family members in treating tuberculosis patients in the Puskesmas Dumbaya Bulan Working Area. This research employs qualitative research with a phenomenological approach. This approach is used to understand individual life experiences toward life goals with data focused on the experience of being involved with family members in treating tuberculosis patients. There are six participants involved and are determined trought data saturation. The results indicate five themes: family knowledge about tuberculosis, family experience in treating tuberculosis patients in the early stages, history of previous experience in treating tuberculosis patients, support while the patients is on tuberculosis treatment, and the risk of treatment failure, and family expectations. The results are expected to provide information about the family’s experience in treating patients to be developed for further research.